KEBIJAKAN PEMERINTAH DAERAH KOTA PEKALONGAN DALAM UPAYA PEMULIHAN INDUSTRI PARIWISATA PADA SITUASI PANDEMI COVID-19 - Fathiyyah Nur Andina (SABBHATÃ YATRA : Jurnal Pariwisata dan Budaya, 2022)
The COVID-19 pandemic that hit Indonesia has affected all sectors, including the tourism industry. The purpose of this study was to review the impact of the COVID-19 pandemic on the tourism industry sector of Pekalongan City and to find out the direction of the Pekalongan City Government's policy regarding industry based on the RPJMD of Pekalongan City for 2021-2026. Qualitative research methods with Miles and Huberman models are data reduction, data presentation, and conclusions. The data source uses secondary data. Pekalongan City tourist arrivals decreased by 60.7% compared to 2019. The decline in the investment value of Pekalongan City in 2019 was Rp. 3.29 Trillion and in 2020 it was Rp. 196.11 Billion. The policy direction of the Pekalongan City Government in restoring the tourism industry as contained in the Pekalongan City RPJMD 2021-2026 is to increase the promotion and empowerment of tourism, industry, trade and services and build a creative economy database based on local potential; improving the quality of human resources for tourism, creative economy, trade, and services that are able to be competitive; collaboration in creating a conducive tourism and creative economy climate; and increasing the role of the community in the development, preservation, promotion of tourism, creative economy, trade, and services while taking into account the carrying capacity and capacity of the environment; Strengthening the causes of the creative economy, tourism, trade, and services. As well as prioritizing development, namely the revitalization of tourism objects, ease of accessibility with the development of the Pekalongan Baru Area and TOD (Transit Oriented Development) Pekalongan Station.